2016
DOI: 10.1111/jph.12501
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Fusarium Wilt and Growth Promotion of Tomato Plants Using Endophytic Bacteria Isolated from Solanum elaeagnifolium Stems

Abstract: Seven culturable bacterial isolates, obtained from the internal stem tissues of Solanum elaeagnifolium and successfully colonizing the internal stem tissues of tomato cv. Rio Grande, were screened for their in vivo antifungal activity against Fusarium oxysporum f.sp. lycopersici (FOL) and their growth‐promoting potential on tomato plants. SV101 and SV104 isolates, assessed on pathogen‐challenged tomato plants led to a significant decrease (77–83%) in Fusarium wilt severity and vascular browning extent (76%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Silva et al [55] observed a biological control of coffee leaf rust caused by Hemileia vastatrix with endophytic bacteria such as Bacillus megaterium and Microbacterium testaceum. In another study, Bacillus cereus decreased wilt symptoms of tomato caused by F. oxysporum [56]. In our study, endophytic bacteria P. putida L2 and S. pavanii L8 were able to reduce lupin root rot caused by F. solani in WMB and MBC amended soil.…”
Section: Discussionsupporting
confidence: 62%
“…Silva et al [55] observed a biological control of coffee leaf rust caused by Hemileia vastatrix with endophytic bacteria such as Bacillus megaterium and Microbacterium testaceum. In another study, Bacillus cereus decreased wilt symptoms of tomato caused by F. oxysporum [56]. In our study, endophytic bacteria P. putida L2 and S. pavanii L8 were able to reduce lupin root rot caused by F. solani in WMB and MBC amended soil.…”
Section: Discussionsupporting
confidence: 62%
“…Biological control agents (BCAs) may be a potential strategy to supplement chemical methods. In recent years, the use of endophytic BCAs in the management of plant disease has gained popularity as an alternative to chemical application, driven in part by concerns for human and environmental safety with the use of fungicides (Chen et al, 1995;Ryan et al, 2008;Cabanás et al, 2014;Rybakova et al, 2015;Aydi Ben Abdallah et al, 2016;Hong and Park, 2016). Endophytes are microorganisms that spend at least parts of their life cycle inside the plant (Hardoim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although Fusarium fungi can invade plants through seeds and wounds, they also enter plants through their roots (Lagopodi et al, 2002; Aydi Ben Abdallah et al, 2016), especially if root cap border cells are damaged (Gunawardena and Hawes, 2002). The disease is managed by crop rotation, planting resistant crops, letting the land lie fallow, and/or applying chemical fungicides.…”
Section: Introductionmentioning
confidence: 99%